FLORÍSTICA DAS PRAIAS DA ILHA DE SÃO LUÍS, ESTADO DO MARANHÃO (BRASIL): DIVERSIDADE DE ESPÉCIES E SUAS OCORRÊNCIAS NO LITORAL BRASILEIRO - Cabral Freire, Maria Cristina C. [UNESP]; Monteiro, Reinaldo [UNESP] (Instituto Nacional de Pesquisas da Amazônia, 1993)
São Luís Island, located in the north of the State of Maranhão is itself a transitional region between the Amazonian and the northeastern floras. With such phytogeographi-cal background, the aim of this paper was to realize a floristic survey on the sandy beaches of the São Luís Island and to compare this 'survey with other areas sampled along the Brazilian coast. A total of 260 species was found, distributed in 76 families, and among these the Fabaceae presenting the highest number of species (24). The floristic comparison showed that the State of Bahia has the highest number of species in common with São Luis (63), followed by the State of Pará (59). Among the species found in São Luís, 125 were exclusive of this area.

A Ilha de São Luís, situada ao norte do Estado do Maranhão, constitui-se numa região de transição entre duas floras distintas: flora amazônica e flora nordestina. Considerando esta peculiar situação fitogeográfica, o objetivo deste trabalho foi realizar o levantamento florístico nas prais arenosas da Ilha de São Luis e compaará-lo com os de outras áreas amostradas no litoral brasileiro. Foram totalizadas 260 espécies, compreendidas em 76 famílias, sendo Fabaceae com o maior número de espécies (24). A comparação floristica constatou que o estado da Bahia apresentou o maior número de espécies em comum com São Luís (63) e, em seguida, o estado do Pará (59). Dentre as espécies amostradas em São Luís, 125 foram exclusivas da região.
Floristics of the Beaches of São Luis Island, State of Maranhão (Brazil): Species Diversity and Occurrence in the Brazilian Coast
Keywords: floristics; beach; diversity; florística; praia; diversidade